1996
DOI: 10.1002/(sici)1096-9861(19960805)371:4<633::aid-cne11>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Postembedding immunocytochemistry demonstrates directly that both retinal and cortical terminals in the cat superior colliculus are glutamate immunoreactive

Abstract: Although the excitatory neurotransmitter glutamate is known to be present in the cat superior colliculus (SC), the types of synapses that contain glutamate have not been examined. We, therefore, studied the ultrastructure of synaptic profiles labeled by a glutamate antibody by using electron microscopic postembedding immunocytochemistry. In addition, unilateral aspiration lesions of areas 17-18 were made at 5-28 days before death in order to determine whether degenerating terminals from visual cortex were glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…To compare the ultrastructure and synaptic targets of RL corticothalamic terminals in the LPN to those of retinogeniculate terminals, in the same LGN tissue that contained labeled cortical terminals, we also examined large profiles that contained loosely packed round vesicles and distinctive pale mitochondria (RLP profiles). This ultrastructure has been found to be specifically associated with retinal terminals (Guillery, 1969; Lieberman and Webster, 1974; Robson and Mason, 1979; Nakamura et al, 1981; So et al, 1985; Hamos et al, 1987; Nunes Cardozo et al, 1991; Luth et al, 1993; Mize and Butler, 1996; Mize, 1996; Klooster and Vresnsen, 1997). Examples of RLP profiles are illustrated in Figure 10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the ultrastructure and synaptic targets of RL corticothalamic terminals in the LPN to those of retinogeniculate terminals, in the same LGN tissue that contained labeled cortical terminals, we also examined large profiles that contained loosely packed round vesicles and distinctive pale mitochondria (RLP profiles). This ultrastructure has been found to be specifically associated with retinal terminals (Guillery, 1969; Lieberman and Webster, 1974; Robson and Mason, 1979; Nakamura et al, 1981; So et al, 1985; Hamos et al, 1987; Nunes Cardozo et al, 1991; Luth et al, 1993; Mize and Butler, 1996; Mize, 1996; Klooster and Vresnsen, 1997). Examples of RLP profiles are illustrated in Figure 10.…”
Section: Resultsmentioning
confidence: 99%
“…We identified retinal terminals in the rat LGN on the basis of their distinctive pale mitochondria. Multiple studies have suggested that pale mitochondria can be used to identify retinal terminals in the LGN, superior colliculus, and pretectum (Guillery, 1969; Lieberman and Webster, 1974; Robson and Mason, 1979; Nakamura et al, 1981; So et al, 1985; Hamos et al, 1987; Nunes Cardozo et al, 1991; Luth et al, 1993; Mize and Butler, 1996; Mize, 1996; Klooster and Vresnsen, 1997). Similar to RL corticothalamic terminals, we observed that retinogeniculate terminals are large profiles that contain round vesicles and are surrounded by a multilayer glial sheath.…”
Section: Discussionmentioning
confidence: 99%
“…We have focused on the superior colliculus because this structure receives a dense glutamatergic projection of retinal axons (Mize & Butler, 1996) and because it displays the highest metabolic response to visual stimuli (Toga & Collins, 1981). Careful observation of the superior colliculus following 3‐D reconstruction revealed an anatomically restricted ‘activated’ volume located within the superficial grey layers.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology for the synthesis of the molecule and its specificity have been reported previously (Madl et al, 1986); (2) a commercially prepared polyclonal antibody raised in rabbit against protein-conjugated glutamate, hereafter abbreviated GLU (Chemicon, Inc., Temecula, CA). Although both antibodies recognize both neurotransmitter and metabolic pools of glutamate, recent studies suggest that moderate to dense labeling in immunocytochemistry experiments reflects the neurotransmitter pools of this amino acid (see Mize & Butler, 1996, for a discussion of this issue).…”
Section: Immunocytochemistrymentioning
confidence: 99%